Development of Inquiry-Based Teaching Materials on Environmental Pollution to Improve High School Students' Environmental Literacy Skills - Vikram, Muhammad; Riandi, Riandi; Solihat, Rini (Jurnal Paedagogy, 2023)
This research aims to produce inquiry-based e-teaching materials on environmental pollution to improve student's literacy skills in terms of validity, effectiveness, and practicality. This study used the research and development (R&D) method with the ADDIE model. This study was carried out in a senior high school in Cimahi. The e-teaching materials trial was conducted in two classes, with the experimental class using e-teaching materials and the control class as a comparison using traditional school textbooks. The e-book validation instrument used in this study was a questionnaire sheet. Validation analysis was the data analysis method employed, and the t-test and N-gain were utilized to examine the effectiveness of the instructional materials. The study's findings demonstrated that the inquiry-based teaching materials on environmental pollution material were declared valid and suitable for use in the biology learning process. According to the outcomes of employing inquiry-based e-teaching resources to enhance environmental literacy abilities, the experimental class's N-gain value was higher than the average n-gain value for the control class. Therefore, inquiry-based online teaching resources are practical and effective at enhancing students' environmental literacy abilities.